2021
DOI: 10.1016/j.msard.2020.102717
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab outcomes by age: Post hoc analysis from the randomized CARE-MS studies over 8 years

Abstract: Background: Alemtuzumab significantly improved clinical and MRI outcomes vs. subcutaneous interferon beta-1a (SC IFNB-1a) in the CARE-MS trials (NCT00530348, NCT00548405), with sustained efficacy in 2 consecutive extensions (NCT00930553, NCT02255656 [TOPAZ]). Methods: Post hoc analysis of 8-year alemtuzumab efficacy and safety in pooled CARE-MS patients (N=811) stratified by baseline age (≥18 to ≤25, >25 to ≤35, >35 to ≤45, >45 to ≤55 years). Results: Compared with SC IFNB-1a over 2 years across age cohorts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…This suggests that the efficacy of alemtuzumab was maintained over the 2-year post-index period as those pwMS not achieving a sufficient response to treatment would be expected to discontinue from treatment or request a further course of treatment. These findings add to those of a previous 8-year post-hoc analysis of the randomized phase III CARE-MS studies showing that 48–53% of pwMS across age cohorts (ranging from 18 to 55 years) received no additional alemtuzumab or DMT beyond the 2-year core study period, and approximately 70% of pwMS remained in the study and received alemtuzumab throughout 8-years of follow-up [ 28 ].…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that the efficacy of alemtuzumab was maintained over the 2-year post-index period as those pwMS not achieving a sufficient response to treatment would be expected to discontinue from treatment or request a further course of treatment. These findings add to those of a previous 8-year post-hoc analysis of the randomized phase III CARE-MS studies showing that 48–53% of pwMS across age cohorts (ranging from 18 to 55 years) received no additional alemtuzumab or DMT beyond the 2-year core study period, and approximately 70% of pwMS remained in the study and received alemtuzumab throughout 8-years of follow-up [ 28 ].…”
Section: Discussionsupporting
confidence: 74%
“…Future research should study whether the high percentage of patients improving in this research could be related to unique cultural and genetic of Colombian people. Understanding the relationship with these variables is important because, as in previous research, this study did not observe a relationship between the effectiveness of alemtuzumab with age (Bass et al, 2021) or with the level of disability at baseline.…”
Section: Discussionmentioning
confidence: 44%
“…These studies concluded that at two years of follow-up (Cohen et al, 2012;Coles et al, 2012), and three years of follow-up (Coles et al, 2008), between 70 and 80% of patients remained free of disease activity. alemtuzumab was not affected by age (Bass et al, 2021).…”
Section: Introductionmentioning
confidence: 79%
“…In terms of clinical research, the current clinical studies on ALZ-related adverse reactions are incomplete. In addition to the CARE-MS trials, more large-scale, multicenter clinical trials should be conducted to obtain additional frontline clinical data ( 26 ). Future clinical research is also expected to incorporate more refined and comprehensive stratifications to derive more reliable and trustworthy conclusions.…”
Section: Discussionmentioning
confidence: 99%